(untitled) (Damascus University Journal of Historical Studies, 2021)
The agony of labourers and farmers in Syria after the French occupation between 1920 and 1946 pushed us to study the affable position in Syria taking the farmers and labourers as a pattern, because the position of labourers deteriorated as a result for ancillary relation between Syria and conquered France. So that, the household workshops crumbled especially after the invasion of foreign goods to the Syrian malls and the facilitations of French authorities by practicing the policy of outspread door. After 1929 cresis the craftsmen developed their metiers by using machines among the foreign competition which was supported by capitalistic systems which linked with the occupier to change the countries into consumer markets having no productions. The sustenance case of labourers had affected negatively on the labours position in Syria through the longtime of working which didn’t proportionate with their low wages in addition to the actuation of boys and women in places impoverishing to the healthy conditions. The farmers layer was calling for despair and depravation especially after snatching their lands and delivering it to France succors when they were mainstay of revolution that attacked the French occupier. But the agriculture labours and farmers how worked at feudals, faced all kinds of persecute and exploitation to get their living morsel.